2016
DOI: 10.1007/s10546-016-0164-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Parametrization of Reynolds Stress and Turbulent Heat Flux in the Stably-Stratified Lower Arctic Troposphere Using Aircraft Measurements

Abstract: Aircraft measurements are used to characterize properties of clear-air turbulence in the lower Arctic troposphere. For typical vertical resolutions in general circulation models, there is evidence for both downgradient and countergradient vertical turbulent transport of momentum and heat in the mostly statically stable conditions within both the boundary layer and the free troposphere. Countergradient transport is enhanced in the free troposphere compared to the boundary layer. Three parametrizations are sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 43 publications
1
33
0
Order By: Relevance
“…3 (100 m) justifies the range of the mean BL height. The mean BL height within its range can be confirmed by results from an extensive study on BL height, mixing and stability during the NETCARE 2014 campaign (Aliabadi et al, 2016a). The capping temperature inversion above 390 m, inferred from values of e , represents a transport barrier for air masses between the BL and the free troposphere (FT).…”
Section: Meteorological Conditions During the Netcare 2014 Campaignmentioning
confidence: 67%
“…3 (100 m) justifies the range of the mean BL height. The mean BL height within its range can be confirmed by results from an extensive study on BL height, mixing and stability during the NETCARE 2014 campaign (Aliabadi et al, 2016a). The capping temperature inversion above 390 m, inferred from values of e , represents a transport barrier for air masses between the BL and the free troposphere (FT).…”
Section: Meteorological Conditions During the Netcare 2014 Campaignmentioning
confidence: 67%
“…Temperature profiles indicated a surface-based temperature inversion of ∼5 ∘ C up to an altitude of 300-400 m ( Figure S6). Aliabadi et al [2016] made similar observations using Polar6 observations and radiosondes to estimate a boundary layer height of 275 ± 164 m. We will refer to the portion of the lower troposphere with a positive vertical gradient in temperature profile as the boundary layer. The median boundary layer wind speed was 4.0 m s −1 compared to 5.1 m s −1 aloft ( Figure S8).…”
Section: Overview Of Meteorological Situationmentioning
confidence: 93%
“…DMS(g) vertical profiles are sensitive to the boundary layer height. For the July 2014 campaign, Aliabadi et al (2016b) reported an average boundary layer height of 275 ± 164 m. They showed that the profiles of the potential temperature exhibited a positive vertical gradient throughout the aircraft campaign (their Fig. 4).…”
Section: Flexpart-ecmwfmentioning
confidence: 94%
“…In July 2014, both the measurements and simulation show a strong decrease in DMS(g) mixing ratios with altitude in the lowest 300 m. Aliabadi et al (2016a, b) estimated the boundary layer height as 275 ± 164 m, using data from radiosondes launched at Resolute Bay and the Amundsen icebreaker, during the 2014 campaign. Aliabadi et al (2016b) indicated that the magnitude of turbulent fluxes of momentum, heat and the associated diffusion coefficients are significantly reduced above the boundary layer height during the 2014 campaign. Thus, we find the strongest vertical gradient between the boundary layer and above.…”
Section: Geos-chemmentioning
confidence: 99%
See 1 more Smart Citation